Pencegahan Kecurangan Berbasis Catur Purusa Artha Di Lembaga Perkreditan Desa (LPD) X - Dewi, Ni Komang Urip Krisna (Politeknik Raflesia Press, 2024)
Village Credit Institution (LPD) is one of the unique financial institutions in Bali. LPD is managed by villagers (banjar). LPD has an important role in supporting the economic growth of the community on the island of Bali. Although LPD has a vital position in Bali, some LPDs have actually gone bankrupt due to poor financial management and fraud prevention. LPD in Bali strives to manage management based on local Balinese values ​​to avoid bankruptcy. One of the local values ​​applied is Catur Purusa Artha. Caturusa Artha is the four goals of human life. The purpose of this study is to analyze fraud prevention based on the philosophical values ​​of Catur Purusa Artha in Village Credit Institutions (LPD). This study uses a qualitative approach with a case study method. Informants are informants at LPD X and other related informants. Data collection was carried out through interviews, observations, and documentation. The novelty in this study is that previous researchers only focused on those based on Tri Hita Karana, researchers tried to explore with different values, namely the values ​​of Catur Purusa Artha.